Propagation patterns of different degree meteorological droughts across the Yangtze River Basin: a three-dimensional drought feature identification approach with Copula modeling - Xing, Lisong; Zhao, Ruxin; Sun, Hongquan; Tan, Zhuoyan; Fang, Qingqing; Li, Ming; Halder, Krishnagopal; Srivastava, Amit Kumar (Journal of hydrology (Amsterdam), 2025)
[Display omitted] •A quantified method to divide different degrees of drought events was proposed in this study.•Extreme drought in the YRB were frequent after 2000.•Severe and extreme droughts in the YRB were concentrated in the middle reaches.•A major extreme drought usually evolves from multiple minor drought events. Extreme droughts have frequently affected the Yangtze River Basin (YRB), significantly impacting agriculture, ecosystems, and socio-economic conditions. However, it is challenging to quantify these drought degrees due to their spatial and temporal complexities, such as varying drought durations, severities, and affected areas. In this study, we proposed a framework to quantify different degrees of drought events combined with different drought characteristics. It consists of a three-dimensional drought feature identification method (longitude-latitude-time continuum identification) and the Copula function. Then, we analyzed the spatial and temporal evolution patterns of drought events of different degrees in the YRB during 1951–2022, and reviewed the occurrence and progression of three notable droughts (in 2006, 2019, and 2022) documented in the YRB. Temporally, the YRB experienced a higher frequency of severe droughts from 1951 to 1980, and an increase in extreme drought events primarily after 2000. Spatially, severe and extreme droughts were concentrated in the middle reaches, whereas moderate and light droughts were more common in the Jinsha River Basin. The east–west migration was the main propagation characteristics of drought patterns at different levels in the YRB. Notably, extreme droughts mostly resulted from the convergence and overlapping of several smaller extreme drought events, creating a significantly larger drought-affected area and higher severity.